Urban appeal the relationship of urbanization and income per capita in the Philippines - Capili, Dominique Marie I.; Hizon, Jelyn Naomi L.
This study explores the relationship between urbanization and the level of income per capita in the Philippines, specifically the role of urbanization economies and select indicators of urbanization, specifically income inequality, gender inequality in the workforce, and access to healthcare, in explaining this relationship. Although there is substantial literature outside the country that supports the hypothesis of this study, there are few in the context of the Philippines - this study aims to contribute to the existing literature and inform policy decisions. Using data from the Philippine Statistics Authority's (PSA) national surveys and censuses for 2015, a cross-sectional multiple linear regression model is used to determine the estimates which revealed that all the indicators or urbanization were significant at varying degrees. The same analysis finds that the percentage of urban barangays, primacy, number of hospitals, and health expenditure of a region is positively correlated to income and gender inequality is negatively correlated to income. The most surprising finding is how the total population of a region is negatively correlated to income per capita despite cited studies on city size and income per capita suggesting the result should be otherwise. This study concludes that (1) there is a need for the national government to begin focusing on urbanizing cities and barangays, (2) there should be policies aimed at reducing the fertility rate, (3) there must be dimensions considered, primarily inequality, in the positive relationship between primacy and income, and (4) structural problems like income inequality, gender inequality in the workforce and differences in access to healthcare are relevant to the analysis of the spatial variation of the level of income per capita.